Phonotactic Competency of Bengali Speaking Children with and without Speech-Language Impairment: Kompetensi Fonotaktik pada Anak-Anak Penutur Bahasa Bengali dengan dan tanpa Gangguan Bicara-Bahasa - Rahman, Istiak; Nijhum, Nisharggo; Naeem, MD Iftekhar Ahmed; Islam, Jahirul; Billah, Masum (Journal of Literature and Education, 2025)
evelopment of phonotactic competency in various contexts of phonological constituents is a prerequisite of effective speech-language competency in the native language. This study aims to explore the phonotactic competency of Bengali-speaking children with and without speech-language impairment. A mixed-method approach exploring the nature of phonotactic competency and differences among those competencies was undertaken. A total of 80 children with typical development (20), autism spectrum disorder (20), down syndrome (20), and language delay (20) were recruited for this study. Typically developing participants statistically outperformed (p< .05) others regarding the production of ranges of syllable structure, clusters, and consonant types, while significant (p< .05) within and between group variability was accounted for in the other groups. Variations in the simplification processes of cluster production and error types across syllable positions were also observed. The findings of the study may facilitate the understanding of phonological development patterns of the study population, suggesting the inclusion of varied cluster simplification patterns to assess phonotactic competence.